Investigating potential associations between O3 exposure and lipid profiles: A longitudinal study of older adults in Beijing. (December 2019) - Li, Ang; Pei, Lu; Zhao, Meiduo; Xu, Jing; Mei, Yayuan; Li, Runkui; Xu, Qun
Abstract: Background: Little information exists on the lipidemic effects of ozone exposure. Few studies have focused on the different patterns of the association among older adults population, and little attention has been given to comprehensive lipid indices when evaluating the effect of O3 exposure on the metabolism. Methods: We conducted a longitudinal study involving 201 older adults in Beijing, China between 2016 and 2018. A mixed regression model was applied with random effects to investigate the relationship between O3 and lipid profiles. Results: O3 exposure positively correlated with TC, LDL-C, CRI-I, CRI-II and AC at short-term and medium-term exposure periods. The largest increases in TC, LDL-C, CRI-I and CRI-II were found in the 28-days moving average indicating accumulative effects over prolonged exposure period. A 10 μg/m 3 increase of O3 at the 28-days moving average was associated with a significant increase of 3.9% (95% CI: 1.0, 6.9) in TC, 8.2% (95% CI: 4.2, 12.4) in LDL-C, 4.8% (95% CI: 1.1, 8.5) in CRI-I and 7.0% (95% CI: 2.7, 11.5) in CRI-II. Stratification by health status and characteristics revealed different patterns of lipid changes among older adults, lipid status, age, sex and BMI may modify the relationship between O3 exposure and lipid profiles. Conclusions: Our findings suggest that short-term and medium-term O3 exposure is associated with lipid profiles abnormalities among the older adults. Evidence also suggests there are patterns within population which differ according to both health status and demographic characteristics. Highlights: Association between ambient O3 exposure and lipid profiles in older adults were assessed. O3 exposure positively correlated with TC, LDL-C, CRI-I, CRI-II and AC at different exposure periods among the older adults. O3 influenced different lipid profiles depending on both health status and demographic characteristics. These results should inform policies to prevent adverse health effects in older adults.